Banning Compensation for Donations of Blood and Blood Components in Ontario - Ansh Goyal (McMaster University Library Press, 2020)
In 2014, Ontario passed Bill 21: Safeguarding Healthcare Integrity Act, which enacted the Voluntary Blood Donations Act, 2014, to ban all forms of compensation for donations of blood and blood components. Ontario justified this action by invoking the principles of the 1997 Krever Commission, which defined blood as a public resource of such value and importance that it must remain under the singular control of an organization that only serves the public interest. This reform was introduced with the intention to prevent another public health disaster like that of the tainted blood scandal in the 1980s, protect voluntary donor pools, and stop potentially exploitative plasma collection techniques. Responding to the licensing of a private plasma collection agency by Health Canada, Ontario met with key stakeholders such as Canadian Blood Services, Canadian Plasma Resources, blood advocacy organizations, and patient groups before finally passing Bill 21. By placing a ban against blood collection agencies besides Canadian Blood Services and by implementing aggressive consequences for violations, Ontario ensured all forms of blood donation would remain voluntary unless deemed necessary by Canadian Blood Services.  Similar bills were introduced with differing outcomes in Alberta, British Columbia, and the Canadian Senate in 2017, 2018, and 2019 respectively. The contentious and varying opinions on blood donation regulation at the provincial and federal levels of government demonstrate that this topic will remain relevant to Canadian politics for the foreseeable future. En 2014, l'Ontario a adopté le projet de loi 21: loi sur la sauvegarde de l'intégrité des soins de santé, qui a mis en exécution et validé la loi sur les dons de sang volontaires, afin d'interdire toutes formes d'indemnisation pour les dons de sang et de composants sanguins. L'Ontario a justifié cette mesure sur la base des principes de la Commission Krever de 1993, définissant ainsi le sang comme une ressource publique d'une valeur et importance telles qu'il doit rester sous le contrôle singulier d'une organisation qui ne sert que l'intérêt public. Cette réforme a été introduite dans le but de prévenir une autre catastrophe de santé publique comme celle du scandale du sang contaminé dans les années 80, de protéger les donneurs volontaires et d'empêcher les techniques de collecte de plasma pouvant conduire à l'exploitation des donneurs. En réponse à l'agrément d'une agence privée de collecte de plasma par Santé Canada, l'Ontario a rencontré des intervenants clés, tels que la Société canadienne du sang, Canadian Plasma Resources, des organisations de défense du sang et des groupes de patients avant de finalement adopter le projet de loi 21. En interdisant la collecte de sang par les agences outre la Société canadienne du sang et en mettant en œuvre un arsenal répressif en cas de violation, l'Ontario a veillé à ce que toutes les formes de don de sang restent volontaires, autres que la Société canadienne du sang juge le contraire nécessaire.  Des projets de loi similaires ont été présentés, avec des résultats différentes en Alberta, en Colombie-Britannique et au Sénat canadien respectivement en 2017, 2018 et 2019. Les opinions tranchées et divergentes des gouvernements provincial et fédéral sur la réglementation des dons de sang aux paliers de gouvernement provincial et fédéral démontrent que ce sujet demeurera d'importance pour la politique canadienne dans un avenir proche.